Exploring the self-care challenges in patients undergoing hemodialysis: A conventional content analysis - Parvaneh Asgari; Esmail Shariat; Mostafa Gholami; Fatemeh Bahramnezhad (Tehran University of Medical Sciences, 2020)
Background & Aim: Self-care plays an important role in the management of care for patients with chronic renal failure. In order to provide effective education, it is necessary to identify problems, concerns and challenges in this group of patients. The aim of this study was to explore the challenges of self-care in the patients undergoing hemodialysis. Methods & Materials: This study is part of a research project on adherence to treatment regimen in hemodialysis patients referred to hospitals affiliated to Tehran University of Medical Sciences in 2019. Patients with the highest and lowest mean (SD) scores of self-care were selected by the purposeful sampling method and finally, 22 in-depth semi-structured interviews were performed with 18 interviewees. All data were recorded, transcribed and analyzed using the conventional content analysis approach proposed by Graneheim and Lundman. Results: Findings from the data analysis included four categories: "the mismatch between the view of patient and the view of nurse", "missing loop training", "culture: a double sword ", and "dual role of religious beliefs". Conclusion: The results of the present study showed that patients undergoing hemodialysis faced many challenges in self-care. They had difficulty in understanding the meaning of self-care and its implications. There is a need to plan for educating these patients and also changing their religious and cultural beliefs.